Effect of Epstein-Barr Virus DNA on the Incidence and Severity of Arthritis in a Rheumatoid Arthritis Mouse Model - Fadlallah, Sukayna; Hussein, Hadi; Jallad, Mary-Ann; Shehab, Marwa; Jurjus, Abdo R.; Matar, Ghassan M.; Rahal, Elias A. (Frontiers in Immunology, 2021)
Objective: We recently demonstrated that EBV DNA is correlated with proinflammatory responses in mice and in rheumatoid arthritis (RA) patients; hence, we utilized an RA mouse model to examine whether EBV DNA enhances the risk and severity of arthritis and to assess its immunomodulatory effects. Methods: C57BL/6J mice were treated with collagen (arthritis-inducing agent), EBV DNA 6 days before collagen, EBV DNA 15 days after collagen, Staphylococcus epidermidis DNA 6 days before collagen, EBV DNA alone, or water. Mice were then monitored for clinical signs and affected joints/footpads were histologically analysed. The relative concentration of IgG anti- chicken collagen antibodies and serum cytokine levels of IL-17A and IFNϒ were determined by ELISA. The number of cells co-expressing IL-17A and IFNϒ in joint histological sections was determined by immunofluorescence. Results: The incidence of arthritis was significantly higher in mice that received EBV DNA prior to collagen compared to mice that only received collagen. Similarly, increased clinical scores, histological scores and paw thicknesses with a decreased gripping strength were observed in groups treated with EBV DNA and collagen. The relative concentration of IgG anti-chicken collagen antibodies was significantly increased in the group that received EBV DNA 6 days prior to collagen in comparison to the collagen receiving group. On the other hand, the highest number of cells co-expressing IFNϒ and IL-17A was observed in joints from mice that received both collagen and EBV DNA. Conclusion: EBV DNA increases the incidence and severity of arthritis in a RA mouse model. Targeting mediators triggered by viral DNA may hence be a potential therapeutic avenue.